Baturaja inscription: a threats to Miańga - Andhifani, Wahyu Rizky; Tedjowasono, Ninny Susanti (Penerbit Universiti Kebangsaan Malaysia, 2024)
Miańga (Minanga) is an area that is now in the administrative region of South Sumatra. This region is a historical area, this is proven by the appearance of this name on two inscriptions, namely the Kedukan Bukit inscription and the Baturaja inscription. One of the newly discovered inscriptions is the Baturaja inscription. In this article, the problem is the description, transliteration, language translation and interpretation of the threat analysis against Minanga in the Baturaja inscription. The method is a qualitative descriptive method that is carried out through inductive analysis from the results that will be analyzed. The Baturaja inscription is one of the inscriptions from the time of the Kedatuan Sriwijaya. The script used is the Pallava script later than Old Malay. This inscription, if seen from its paleographic form, most likely originates from around the VII century, like the early inscriptions of the Sriwijaya Kingdom, namely: the Kedukan Bukit inscription, the Talang Tuwo inscription, the Telaga Batu inscription, the Kota Kapur inscription, the Karang Brahi inscription, the Palas Pasemah inscription, and some the short Siddhayatra inscription. The content of this inscription is related to the curse in the Minanga area that is not devoted to Sriwijaya. This is the first curse inscription or oath, or threat issued by Kedatuan Sriwijaya.